The mode of insertion of umbilical cord and vessels: association with maternal haemoglobin genotype, neonatal factors, and placental component volumes - Addai, F.K.; Quashie, F.J.; Ockleford, C.D. (Anatomy and Embryology, 1994)
We investigated whether variations in mode of attachment of umbilical cords and vessels coincided with differences in maternal haemoglobin genotype and neonatal factors or placental micro-volumetric composition. The incidence of placentae with marginally inserted cords, or those in which umbilical vessels separated prior to insertion, was not statistically different in samples from sickle cell patients having haemoglobin-SS and haemoglobin-SC genotypes, as compared with haemoglobin-AA controls. Results obtained from analysis of variance (ANOVA) suggest that the mode of insertion (status) of umbilical vessels may have clinical significance, because it produced differences in the main effects associated with neonatal gestational age, placental weight, and placental index. Point counting stereology was employed to estimate the microscopic compartment volumes of placentae prior to an assessment of statistical association between the data obtained and the status of umbilical vessels and maternal haemoglobin genotype. Furcate placentae (with separated umbilical vessels) had statistically greater than normal volumes of villi, villous trophoblast, and syncytial knots. We deduce that furcate placentae are prone to early delivery, because they are heavier, having more voluminous villi with more trophoblast and syncytial knots than controls.